THE EFFECTIVENESS OF SCIENTIFIC BASED LEARNING TOWARDS SCIENCE PROCESS SKILL MASTERY OF PGSD STUDENTS (Jurnal Pendidikan IPA Indonesia, 2015)
The purpose of this research is to find out the whether there is difference of science process skill (SPS) mastery and students’ achievement between students who joined class that used scientific based learning method and ones that joined conventional method. The method of this research is Quasi-Experimental Design with static group design. The result showed that there was a significant improvement of SPS mastery by applying scientific based learning, while the improvement of conventional learning class was not quite significant. So, it can be concluded that there was a significant improvement of sig = 0,003 between students’ SPS mastery that joined scientific based learning compared to that joined conventional learning.